ISLAMISME DAN KONSTRUKSI GERAKAN POLITIK PARTAI KEADILAN SEJAHTERA DAN HIZB TAHRIR INDONESIA DI SULAWESI SELATAN - Karim, Syahrir (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
In the scheme of organization, Prosperous Justice Party (PKS) and Hizb Tahrir Indonesia (HTI) are historically and ideologically bound in a solid emotional relationship. The two organizations are basically rooted in a transnational Islamic movement although in later devel- opment they ultimately develop their movements in different spheres; PKS focuses at the level of intra parliamentary with a formal political label whereas HTI concentrates at the level of extra parliamentary as a non-formal organizational movement. HTI, which openly refuses the system of democracy, as a matter of fact benefits significantly from de- mocracy in Indonesia as a “political blessing.” HTI strongly criticizes the system of democracy in Indonesia and as a substitute proposes the system of Khilafah. Ironically, HTI gains freedom to perform its move- ment, to speak, and to campaign as Indonesia applies democracy.